2010
DOI: 10.1074/jbc.m109.048785
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CRM1-mediated Nuclear Export of Transcription Factors by Leukemogenic NUP98 Fusion Proteins

Abstract: NUP98 is a nucleoporin that plays complex roles in the nucleocytoplasmic trafficking of macromolecules. Rearrangements of the NUP98 gene in human leukemia result in the expression of numerous fusion oncoproteins whose effect on nucleocytoplasmic trafficking is poorly understood. The present study was undertaken to determine the effects of leukemogenic NUP98 fusion proteins on CRM1-mediated nuclear export. NUP98-HOXA9, a prototypic NUP98 fusion, inhibited the nuclear export of two known CRM1 substrates: mutated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…3A). It has been reported that Nup98 fusion proteins stimulate NFAT (nuclear factor of activated T cells)-and NF-B-mediated transcription activities by impairing the function of XPO1 (52). Thus, we examined the effects of Nup214 fusion proteins on the NF-B signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…3A). It has been reported that Nup98 fusion proteins stimulate NFAT (nuclear factor of activated T cells)-and NF-B-mediated transcription activities by impairing the function of XPO1 (52). Thus, we examined the effects of Nup214 fusion proteins on the NF-B signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, both NUP98-HoxA9 and NUP98-DDX10 impair the nuclear export of critical transcriptional regulators, leading to their aberrant nuclear retention and enhanced transcription from responsive promoters. 35 The functional significance of deregulated expression of Hox genes has been suspected in the oncogenic processes of some [17][18][19][20][21] but not all 8,9 NUP98 fusion proteins. Although the expression of HoxA genes was sustained in NUP98-CCDC28A-expressing leukemic cells, this may be related to the enrichment for immature myeloid cells in these populations compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…S6). We have previously shown that NUP98-HOXA9 up-regulates NFB-mediated transcription (28). NFB plays a role in erythroid differentiation: it is overexpressed in early erythroid progenitors but is down-regulated during erythroid maturation (59,69).…”
Section: Discussionmentioning
confidence: 99%
“…pGEX6P1-AES, pcDNA3-FLAG-AES, and MSCV-IRES-YFP-FLAG-AES were constructed by subcloning PCR-amplified AES cDNA from pMyr-AES. The construction of NUP98-HOXA9 deletion mutants (28), pGL4.11-KBTBD10 (22), and MSCV-IRES-GFP-HA-NUP98-HOXA9 (25) are described elsewhere. The construction of full-length and deletion mutants of NUP62 and NUP153 are described elsewhere (31).…”
Section: Methodsmentioning
confidence: 99%